Pengaruh Tingkat Konsentrasi Belajar Siswa Terhadap Hasil Belajar Matematika di Sekolah Dasar - Ida, Nur; Halistin, Halistin; Ilham, Muhammad (IAIN Kendari, 2023)
Disruption of study concentration has an impact on the low mathematics learning outcomes of fifth grade elementary school students. This research aims to find out the level of concentration of fifth grade elementary school students, to determine their learning outcomes, and to figure out the effect of concentration levels on the mathematics learning outcomes of the students. This research is a quantitative research using survey method. The population in this study were all fifth-grade students at one of the public elementary schools in Kendari as many as 147 students. The sample in this study was 60 students who were determined by proportional random sampling technique which then analyzed descriptively and inferentially. The results showed that the percentage of data on students’ concentration in the mathematics learning process was in the high category with an average value of 88,63. The percentage of students’ mathematics learning outcomes variable data is 33.33% with an average value of 81.86. Students’ learning concentration significantly influences the mathematics learning outcomes of fifth-grade students at one of the public elementary schools in Kendari. Based on value of Tcount is greater than T table (7,342 > 1,671). The learning concentration contributes of 48,2% to the variable student mathematics learning outcomes.Keywords: Study concentration, mathematics learning outcomes, elementary school